Методи та моделі надання послуг в гетерогенних розподілених інформаційно-телекомунікаційних системах - Лаврів, Орест Андрійович (Національний університет "Львівська політехніка", 2018)
Дисертація присвячена структурно-функціональному синтезу та наданню послуг в гетерогенних розподілених інформаційно-телекомунікаційних системах з метою покращення значень метрик якості надання послуг шляхом оптимізації структури та показників ефективності функціонування телекомунікаційної підсистеми, а також підвищення захищеності, відмовостійкості та зниження тривалості відновлення працездатності інформаційної підсистеми. У роботі проведено аналіз процесу надання послуг в гетерогенних розподілених інформаційно-телекомунікаційних системах. Розроблено та удосконалено методи побудови та моделі гетерогенних розподілених інформаційно-телекомунікаційних систем. Запропоновано методи структурно-функціонального синтезу телекомунікаційної підсистеми інформаційно-телекомунікаційних систем. Удосконалено метод керування конфігурацією та забезпечення катастрофостійкості інформаційної підсистеми інформаційно-телекомунікаційних систем. Розроблено нові та покращено відомі моделі надання послуг в гетерогенних інформаційно-комунікаційних системах. Досліджено особливості побудови та поведінки складної інформаційно-телекомунікаційної системи під впливом зростання навантаження на підставі програмно-реалізованих моделей та експериментального методу дослідження. За сукупністю та новизною отриманих результатів розв’язано актуальну наукову проблему розроблення методів та моделей надання послуг у гетерогенних розподілених інформаційно-телекомунікаційних системах для підвищення якості обслуговування та покращення структурно-функціональних параметрів і характеристик цих систем з метою узгодження взаємодії сервісного шару та шару передавання даних. The thesis is dedicated to the aspects of structural and functional synthesis and the services provision in heterogeneous distributed information and telecommunication systems to improve the metrics of the service quality of delivery by optimizing the structure and indicators of the efficiency of the functioning of the telecommunication subsystem, as well as increasing the security, fault tolerance and reducing the duration of the recovery of the information subsystem. The first chapter analyzes the influence of the system architecture of distributed heterogeneous information and telecommunication systems on their quality metrics. The processes of communication in distributed heterogeneous informationcommunication systems are analyzed, considering the application layer influence. The analysis performed is the basis for further implementation of the tasks of developing models of components of the investigated information and telecommunication systems and methods of providing services in such systems. The second chapter of the thesis proposes a mathematical model for query forwarding in heterogeneous service-oriented systems. The problem of resources allocation of heterogeneous information and communication systems between service flows is stated. Based on the area-based model of service delivery, a set of user’s coordinates was calculated, users are classified by a speed criterion, and that provides the centralizing service management under the overloads of network segments. The calculated parameters of communication processes allow to characterize the process of providing services in the system by calculating the losses probability and system availability. The proposed method of load balancing with multi-stage switching of service points increases the availability of information resources during periods of peak load by 14%. The task of providing data streams with satisfactory service is to optimally combine the physical and logical network structures. The third chapter contains the research of configurations of network topologies based on the theory of graphs. The research of the architecture of a telecommunication channel supported by a set of service classes was performed. The solution of the resource allocation problem between network service flows is proposed in case of equal competition for available physical resources. The goal is to estimate the maximum number of clients who can use the service with different levels of service quality. The problem is formulated in graph theory terms and solved by the method of linear programming for a given network graph. The influence of the logical structure on the availability of network resources is investigated. The proposed method detects redundancy in the physical structure and reduces the cost of the network or changes the routing policy by introducing k-route routing through unused channels, and as a result – by increasing network performance. The fourth chapter presents a new model of the corporate client of the information and communication system. A new model of shared cloud infrastructure has been developed. Both models are implemented as a software and allow to simulate the system performance without its actual building. The information security system as IaaS service in the telecommunication segment of the distributed heterogeneous information and telecommunication system was developed and investigated. The results show that the impact of attacks on the information and telecommunication system has been reduced by more than 90%. The process of infrastructure recovery after catastrophes based on manual and automatic activity is explored. We have estimated the recovery duration in the case of manual and automatic recovery based on the IaaC. The benefit ration may be by an order. The fifth chapter analyses the process of continuous integration and the architecture of its implementation. We offered the advanced method of fully ordered group communication, which keeps the synchronization process operational, even if the message of the sender process is lost. The adequacy of the software component model was verified by studying the routing of multiservice information flow with the hardware router and the software component of the heterogeneous distributed information and telecommunication system. We proved that load balancing in the integrated information service deployment management system could reduce the average duration of queries up to 3 times. We designed an IPTV streaming model. The comparative estimations of the delay are given, which allow to assert that the increase of the channel capacity by 10 times leads to up to 2,5 time decrease in the service delivery delay, which is explained by the restrictions of the load balancing method. The sixth chapter of the thesis presents the methods for deploying cloud infrastructure based on the PaaS principle. The advanced three-layered architecture of information and telecommunication systems with is offered. The study of the of cloud services availability in information and telecommunication systems with multicomponent cloud infrastructure has been conducted. We performed the load testing of the distributed heterogeneous information and telecommunication system based on the cloud infrastructure. The results of load testing revealed a bottleneck in the system. We also simulated utilization of infrastructure components and metrics of service quality and quality of experience. It has been shown that updating of the system code makes it impossible to design and use universal models of the system, since even minor changes to the code which logically combine the components of the system leads to a change in the behavior of the system, which cannot be considered in both analytical and simulation models. In this regard, the proposed methodology for the investigation of distributed heterogeneous information and telecommunication systems based on cloud infrastructure is an important tool in their design and operation and allows solving the problem of harmonizing the levels of the proposed conceptual structure of information and telecommunication systems with improvement of service quality metrics and optimal distribution of resources of such systems. This indicates the achievement of the thesis objectives. Диссертация посвящена структурно-функциональному синтезу и предоставлению услуг в гетерогенных распределенных информационно-телекоммуникационных системах с целью улучшения показателей качества предоставления услуг путем оптимизации структуры и показателей эффективности функционирования телекоммуникационной подсистемы, а также повышения защищенности, отказоустойчивости и снижения продолжительности восстановления работоспособности информационной подсистемы. В работе проведен анализ процесса предоставления услуг в гетерогенных распределенных информационно-телекоммуникационных системах. Разработаны и усовершенствованы методы построения и модели гетерогенных распределенных информационно-телекоммуникационных систем. Предложены методы структурно-функционального синтеза телекоммуникационной подсистемы информационно-телекоммуникационных систем. Усовершенствован метод управления конфигурацией и обеспечения катастрофоустойчивости информационной подсистемы информационно-телекоммуникационных систем. Разработаны новые и улучшены известные модели предоставления услуг в гетерогенных информационно-коммуникационных системах. Исследованы особенности построения и поведения сложной информационно-телекоммуникационной системы под влиянием роста нагрузки на основании программно-реализованных моделей и экспериментального метода исследования.
Methods and models of service provision in heterogeneous distributed information and telecommunication systems
Методы и модели предоставления услуг в гетерогенных распределенных информационно-телекоммуникационных системах
Keywords: розподілена гетерогенна інформаційно-телекомунікаційна система; балансування навантаження; якість надання послуг; навантажувальне тестування; cloud-інфраструктура; міжрівнева взаємодія; distributed heterogeneous information and telecommunication system; load balancing; quality of service provision; load testing; cloud infrastructure; inter-level interaction; распределенная гетерогенная информационно-телекоммуникационная система; балансировка нагрузки; качество предоставления услуг; нагрузочное тестирование; cloud-инфраструктура; межуровневое взаимодействие; 621.391